Pharmacology of Carissa carandas leaf extract: anti-proliferative, antioxidant and antimicrobial investigation. (4th May 2021) - Pathak, Gauri; Singh, Shilpi; Singhal, Mohit; Singh, Jyoti; Hussain, Yusuf; Gupta, Madhuri; Meena, Abha; Gupta, Pratima; Rout, Prasant Kumar
Abstract: Carissa carandas (Apocynaceae), a tropical plant popularly known as karonda in India, is being commonly used as a condiment in pickles and spices. Many usages of the leaf have been described in the traditional system of medicine. However, this part of the plant has not been experimentally investigated comprehensively. Therefore, this study aimed to investigate the anti-proliferative, anti-microbial, and antioxidant potential of leaf extracts. The extracts were prepared in polar and non-polar solvents, and their anti-proliferative potential was tested by 3-(4, 5-dimethylthiazol-2-yl)-25-diphenyltetrazolium bromide assay in cancer/normal cell-lines. The antioxidant activity was estimated by performing various assays, and agar-disk-diffusion assay was used to explore the antimicrobial properties against six gram-positive and five gram-negative bacteria. Among all, methanol and methanol-water extract showed potent radical-scavenging, ferric-reducing, and antioxidant activity. Both the extracts inhibited the growth of cancer cell lines and showed moderate activity against Staphylococcus aureus, Streptococcus mutans, and Mycobacterium smegmatis in a dose-dependent manner. The active extracts were evaluated for in vivo toxicity and found safe up to 2000 mg/kg body weight in mice. Furthermore, methanol and methanol: water extracts were also tested for mutagenicity and found to be non-mutagenic. Hence, these findings suggest anti-proliferative, antioxidant, and antimicrobial potential of C. carandas leaf extracts.